2017
DOI: 10.1371/journal.pone.0170681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protective Efficacy of Poly I:C as an Adjuvant for H9N2 Subtype Avian Influenza Inactivated Vaccine and Its Mechanism of Action in Ducks

Abstract: Current commercial H9 avian influenza vaccines cannot provide satisfactory protective immunity against antigenic variant influenza viruses in ducks. Poly I:C, when used as an adjuvant, improves humoral and cellular immunity in many animals but has not been tested in ducks. In this study, we investigated the protective efficacy of Poly I:C as an adjuvant for an inactivated H9N2 Avian influenza vaccine in ducks. We found that an H9N2 vaccine administered with poly I:C (H9-PIC vaccine) induced a significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In the same study, the adapted virus showed deletions in the stalk region of the NA, which is consistent with field observations of natural adaptation of influenza viruses in poultry (Hossain et al 2008). A handful of pathogenesis studies have been also conducted in turkeys (Morales et al 2009;Bonfante et al 2013;Umar et al 2015), chukars (Zhu et al 2018b), ducks (Zhang et al 2017a;Zhu et al 2018b;Wang et al 2019;Yang et al 2019), and guinea fowl (Umar et al 2016). In general, nonpoultry-adapted H9 IAVs showed limited replication and transmission in gallinaceous birds (Xu et al 2012;Suarez and Puscha 2019).…”
Section: Clinical Signs Pathology and Interspecies Transmissionsupporting
confidence: 81%
“…In the same study, the adapted virus showed deletions in the stalk region of the NA, which is consistent with field observations of natural adaptation of influenza viruses in poultry (Hossain et al 2008). A handful of pathogenesis studies have been also conducted in turkeys (Morales et al 2009;Bonfante et al 2013;Umar et al 2015), chukars (Zhu et al 2018b), ducks (Zhang et al 2017a;Zhu et al 2018b;Wang et al 2019;Yang et al 2019), and guinea fowl (Umar et al 2016). In general, nonpoultry-adapted H9 IAVs showed limited replication and transmission in gallinaceous birds (Xu et al 2012;Suarez and Puscha 2019).…”
Section: Clinical Signs Pathology and Interspecies Transmissionsupporting
confidence: 81%
“…The inhibition of the virus replication in poly(I:C)-treated WT cells ( Figure 4 ) is in agreement with previous reports showing poly(I:C)-induced block of IAV and Marek's disease virus replication in chicken cells ( Ahmed-Hassan et al., 2018 ; Bavananthasivam et al., 2018 ). Polyinosinic:polycytidylic acid also has shown promising results in live birds when used as a prophylactic agent or an adjuvant in vaccines against influenza and Marek's disease ( Parvizi et al., 2012 ; St. Paul et al., 2012 ; Zhang et al., 2017 ). Although the level of poly(I:C)-mediated TLR3-dependent virus reduction ( Figure 4 ) corresponded well with the expected sensitivity to type I interferons (high, moderate, and low sensitivity for VSV, IAV, and ARV, respectively) ( Sekellick et al., 2000 ), other cytokines and antiviral mechanisms may have been involved.…”
Section: Discussionmentioning
confidence: 99%
“…LPAI can break species barrier and cause infection in pig, horse, and human [9]. Vaccination is a good policy for infectious diseases such as avian influenza virus because it reduces complications of AIV in bird [10,11]. The chemically inactivated influenza virus vaccines provide surface antigens or split product.…”
Section: Introductionmentioning
confidence: 99%